Application of polyether ether ketone in obturator telescopic prosthesis fabrication: а case report - Radosavljević, Radivoje; Tabaković, Saša Z.; Todić, Jelena; Mitić, Ankica; Djordjević, Nadica; Lazić, Vojkan; Dubovina, Dejan (Vojnosanitetski pregled, 2023)
Introduction. The retention, stability, and plaque resistance of the obturator prosthesis significantly impact the improvement of the patient’s quality of life. The aim of this paper was to draw attention to the benefits of telescopic obturator prostheses made of polyether ether ketone (PEEK). Case report. We present an approach to the telescopic obturator fabrication using PEEK as the material of choice for the primary and secondary telescopic crowns, which are an integral part of the framework, in a 65-year-old patient with partial maxillectomy. The positioning of the teeth was made with a silicone key, and the featuring of the gingival part of the prosthesis was performed by a composite. Conclusion. PEEK is a polymer with good mechanical and chemical properties besides being biocompatible. An obturator prosthesis made of this material does not incur enormous fabrication costs, and its satisfactory functionality contributes to the improvement of patients’ lives.
Keywords: crowns; dental prosthesis; polyetheretherketone; polymers